Review locally tailored ELT textbooks to meet primary students’ need: Textbooks development - Ratri, Devinta Puspita; Tyas, Peptia Asrining (JEES (Journal of English Educators Society), 2022)
Since there is an emerging issue to strengthen students' local identity particularly in expanding circle countries in the midst of globalization, local culture integration in English language teaching (ELT) has lately grown to answer the challenge. Regarding the case, this study presents a textbook development with local culture integration in ELT for young learners as an effort to build students’ identity at early ages. It exposes that local culture integration can be inserted to all units in the textbooks for primary students which complement the theme-based curriculum as mentioned in the Ministry of Education and Culture Regulation No. 22 Year 2016. It implies that English textbooks with local culture integration may be modified as a viable and acceptable technique of addressing learners' local cultures while learning foreign language. Further, this textbook development provides current guidance for English teachers on how local culture integration in ELT might increase the energy, motivation, and reasoning for Indonesian young learners to learn English in a meaningful context. HIGHLIGHTS: The sections developed in Among Tani English (learning objectives, brainstorming, materials, students’ activities, evaluation) are considered to be sufficient to meet its purpose as a guideline to provide input and teaching activities to assist students' English proficiency. “Among Tani” English textbook is designed in accordance with the thematic-based curriculum for primary school and the topics chosen help students in relating to other disciplines by having a comparable variety of themes to be covered to provides young learners with materials that they are acquainted with. This textbook’s coverage of local culture is based on the environment surrounding students in order to develop students’ cognition, character education, teach students to face threats from outside, and provide students with an overview of community life.